Stereotype, Prejudice And Social Distance In Multiethnic Society - Masdar, Muhammad; Harifuddin, Harifuddin (International Journal of Educational Research & Social Sciences, 2023)
Social harmony is embodied condition of their togetherness, shared values, shared expectations prevailing in social life. In that context, the symbol of interaction used to understand the process of how individuals primarily from various ethnic interpreted and give meaning to the symbols concerning the events and situations in everyday life interaction. In the process of inter-ethnic interaction, individuals influenced by their perceptions of other ethnic groups. The elements in the concept of the interaction of these perceptions are stereotypes, prejudices, and social distance. These three aspects are mental-creative dimensions and the basis of the ongoing process of interaction of quality and sustainable. Stereotyping is often also called "labeling" or a character attribute attached to something individuals, groups, ethnic, and tend to be negative. A consequence of prejudice arises from the stereotype. For example, the Javanese has a stereotype as a polite person, Makassar people considered character hard. These stereotypes born of prejudice, such as ethnic Java will prejudice soft polite when talking while ethnic Makassar prejudice speaks loudly. This condition raises two distinct social distances, for example to the Javanese tend to be more approachable because of his "bad" to be heard over the ethnic Makassar.